Gerenciamento de conflito numa reunião empresarial - Fernandes, Lindinalva Zagoto (2006)
Leadership is a complex concept and has been studied under many perspectives by means of several disciplines, given the importance of understanding the management style that enables businesses to answer quickly to the market requirements. In this perspective, the present study aims to analyze the strategies adopted by a leader for the management of conflicts arising during the business-oriented interlocutions in the course of a meeting of a real state company hosted in a middle class neighborhood of the West zone of the city of São Paulo. The strategies identified by Holmes & Marra (2004) as well as others we had seen used in the discursive practices in order to exert leadership and to keep the involved faces, are examined on the basis of a corpus of 1043 conversational turns. The corpus belongs to the database of project DIRECT - LAEL- PUCSP and is inserted in the research line Language and Work. The study is characterized as an interpretativist analysis and has as theoretical support the principles of Systemic-Functional Linguistics (Halliday, 1985; 1994), Critical Linguistics (Fowler et al., 1979), the Theory of Politeness (Brown & Levinson, 1987) and Analysis of Conversation (Sacks et al., 1974), for we think it is relevant, following Eggins & Slade (1997), to adopt an eclectic theoretical base that extract insights these different approaches have to offer. The study came to confirm the use of the strategies of prevention and deviation of conflict, resolution by negotiation and resolution by imposition (Holmes & Marra, 2004). Data allowed the identification of three other strategies: conflict resolution by contesting, by concession and by partnership, used to make possible both the exercise of leadership and the protection of the faces and interpersonal relationships involved in the interaction